Local Politics and the Formation of Sub-National Imagined Communities: - Metera, Gde Dwitya Arief (Kawalu: Journal of Local Culture, 2015)
This essay looks at two cases of cyber citizen organizations namely Tabanan Lovers and Buleleng jengah. The two cyber citizen organizations emerged from some initiatives to organize members of Facebook community who come from the same hometown, namely Tabanan and Buleleng regency in Bali. In their later development, the two Facebook groups evolve into a space as well as a medium for the cyber citizens to voice their critical political aspiration. Early observation shows that the two groups share similar characteristic of becoming âimagined communitiesâ mediated by not necessarily print media, but instead social media like Facebook. A question that this essay would like to suggest as a future research agenda is what necessitates the formation of these âsubnational imagined communitiesâ which takes place at the regency level and not at provincial level? Through tracing the history of their conception and through online participatory observation, this essay aims at providing a preliminary discussion to help illuminate the formation of these two sub-national âimagined communitiesâ. More specifically, the discussion points to a link connecting local politics of pilkada and the formation of Tabanan Lovers and Buleleng jengah. Keywords: Local Politics, Tabanan, Bali, Buleleng Jengah